2010
DOI: 10.1080/14789949.2010.483284
|View full text |Cite
|
Sign up to set email alerts
|

The relation between dimensions of personality and personality pathology and offence type and severity in juvenile delinquents

Abstract: The relation between dimensions of personality and personality pathology and offence type and severity in juvenile delinquents Nederlof, E.; van der Ham, A.; Dingemans, P.M.A.J.; Oei, T.I. General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Personality problems are also prevalent (Nederlof, van der Ham, Dingemans, & Oei, 2010). Detained adolescents with mental health problems are at increased risk of a range of adverse outcomes including premature mortality, suicide and death from other causes Rodway, Norrington-Moore, While et al, 2011), drug and alcohol problems (Chassin, Knight, Vargas-Chanes, Losoya, & Naranjo, 2009;McClelland, Elkington, Teplin, & Abram, 2004;Neighbors, Kempton, & Forehand, 1992;Palmer, Jinks, & Hatcher, 2010;Sacks et al, 2009), and increased rates of reoffending (Hollander & Turner, 1985;Ramchand, Morral, & Becker, 2009;Walter, Wiesbeck, Dittmann, & Graf, 2011).…”
Section: Psychiatric Disorders In Adolescent Boys In Detention: a Prementioning
confidence: 99%
“…Personality problems are also prevalent (Nederlof, van der Ham, Dingemans, & Oei, 2010). Detained adolescents with mental health problems are at increased risk of a range of adverse outcomes including premature mortality, suicide and death from other causes Rodway, Norrington-Moore, While et al, 2011), drug and alcohol problems (Chassin, Knight, Vargas-Chanes, Losoya, & Naranjo, 2009;McClelland, Elkington, Teplin, & Abram, 2004;Neighbors, Kempton, & Forehand, 1992;Palmer, Jinks, & Hatcher, 2010;Sacks et al, 2009), and increased rates of reoffending (Hollander & Turner, 1985;Ramchand, Morral, & Becker, 2009;Walter, Wiesbeck, Dittmann, & Graf, 2011).…”
Section: Psychiatric Disorders In Adolescent Boys In Detention: a Prementioning
confidence: 99%
“…Um total de 13 artigos tiveram como objetivo identificar perfis com relação a características psicológicas em adolescentes infratores (Aebi et al, 2015;Aebi et al, 2016;Alarcon et al, 2005;Blackburn, 2000;Cauffman et al, 2004;Decuyper et al, 2013;Edens et al, 2011;Espelage et al, 2003;Nederlof et al, 2010;Stefurak & Calhoun, 2007;Stefurak et al, 2004;Taylor et al, 2006;Vinet & Bañares, 2009). Cinco desses se propuseram a investigar diferenças no campo psicológico entre adolescentes infratores utilizando o mesmo instrumento, o Inventário Clínico para Adolescentes de Millon (MACI) que, embora constitua um inventário de avaliação de personalidade geral, é muito utilizado para estudar delinquência juvenil em razão de algumas de suas escalas.…”
Section: Perfis Psicológicosunclassified
“…Nesses se verificou que os diferentes perfis psicológicos não se mostraram associados a diferentes tipos de delitos. Apesar disso, é pontuar que os autores buscaram uma relação entre os perfis psicológicos e os delitos oficiais, o que não necessariamente expressa o padrão comportamental de delitos dos adolescentes, como já se demonstrou em outras pesquisas da área (Taylor et al, 2006;Nederlof et al, 2010). Nederlof et al (2010) também discutem que a compreensão da trajetória do comportamento delituoso é mais importante que a análise dos delitos oficiais.…”
Section: Perfis Psicológicosunclassified
“…The result was similar in the case of 216 high school students between 16 and 19 years old (108 girls and 106 boys) who were attending a Catholic school in New South Wales, identifying a significant negative correlation between agreeableness and interpersonal violence (for both sexes), and in the case of boys, a significant negative correlation was also highlighted between agreeableness and vandalism/theft (Heaven, 1996). Nederlof et al (2010) however, assessing the relationship between personality, the type of charges (crime against morality/against life/violent/violent with property/property), and the severity of the crime in a sample of 108 boys between 12-21 years old in custody in a detention center in the Netherlands, remanded in custody or sentenced to detention without compulsory treatment, showed that none of the five personality dimensions was significantly associated with the type or severity of the offense.…”
Section: Results Obtained From Samples Made Up Of Young Peoplementioning
confidence: 62%